Removal of Glyphosate with Nanocellulose for Decontamination Purposes in Aquatic Systems - da Silva Lessa, Suzan [UNESP]; Orsi, Blenda Lopes [UNESP]; de Oliveira, Luciana Camargo; Botero, Wander Gustavo; Tonello, Paulo Sergio [UNESP]; Goveia, Danielle [UNESP] (MDPI, 2024)
(1) The excessive and incorrect use of agricultural pesticides has caused environmental pollution, with a final destination in aquatic environments. Among the widely used agricultural pesticides, glyphosate stands out for weed control, which according to the World Health Organization (WHO) is potentially carcinogenic in humans. Once in an aquatic environment, decontamination aimed at removing the pesticide is not always a simple task. In this sense, it is necessary to develop low-cost, sustainable procedures with a high remediation capacity. (2) In this context, a nanocellulose-based biopolymer was developed to removal glyphosate from aquatic environments. Nanocellulose was obtained from a cellulose sample from eucalyptus wood and was characterized by scanning and double-beam electron microscopy, scanning microscopy with an energy dispersive detector and Fourier transform infrared (FTIR) spectroscopy. Adsorption studies were carried out to evaluate the retention of glyphosate by nanocellulose. (3) Nanocellulose showed a value of 4.7 mg of glyphosate per gram of nanocellulose, and organomodified nanocellulose showed the removal of 6.1 mg of glyphosate per gram of nanocellulose, as evaluated in pseudo-first-order kinetic models. (4) The biomaterial has a sustainable and renewable origin, has potential for contaminant removal and can be applied to contaminated aquatic systems.